PENDAMPINGAN PENGELOLAAN ZAKAT, INFAQ, SEDEKAH, WAKAF, DAN DANA SOSIAL DI PONDOK PESANTREN AL-IHSAN RIAU - Hikmatullah; Irwandi; Asmarika; Wage; Ali Wardana; Mukhlis (LPPM STAI Muhammadiyah Probolinggo, 2025)
This community service activity aims to enhance the capacity of managing zakat, infaq, sadaqah, waqf, and social funds at Pondok Pesantren Al-Ihsan Riau. The research method used is qualitative with a descriptive-participatory approach, in which the implementing team was directly involved in the mentoring process. Data were collected through observation, in-depth interviews, and documentation. The research subjects included the pesantren leaders, zakat and waqf unit managers, senior students, and beneficiary communities.The results show that the mentoring activities improved the administrators’ understanding and skills in administration, transparency, and accountability of social fund management. In addition, the program encouraged the participation of students and the community in practicing professional management of funds oriented toward community empowerment. In conclusion, mentoring in the management of zakat, infaq, sadaqah, waqf, and social funds at the pesantren contributed positively to strengthening sustainable sharia financial governance and generated significant social impacts for the surrounding community.